Analysis Of Service Quality Attributes Towards Customer Purchase Intention Of Creative Workshops - Luthfia Ahdiani; Annisa Rahmani Qastharin (Innovative: Journal Of Social Science Research, 2023)
EksplorAksi is confronted with the crucial task of enhancing service quality, indicated by lower ratings, negative reviews, and reduced repeat participation. Therefore, this research aims to identify the relationship between service quality dimensions (tangibility, empathy, assurance, responsiveness, and reliability) with customer purchase intention in the context of creative workshops. The primary focus of this research is EksplorAksi, a creative workshop organizer based in Bandung. The data collected from EksplorAksi’s workshops participants (N = 214) were analyzed using the multiple linear regression method. The results indicate a significant relationship between all service quality dimensions and customer purchase intention. The research findings offer recommendations for EksplorAksi to improve customer purchase intention by focusing on tangible and intangible elements. The specific sample size of EksplorAksi’s participants may restrict the generalizability of the findings to other industries. Future research should consider examining the impact of new technologies to improve service quality in creative workshops.